Comparative study of interfacial behavior for polyphosphazene based polymer electrolytes and LiPF6 in EC/DMC against lithium metal anodes. (July 2019) - He, Xuan; Schmohl, Sebastian; Wiemhöfer, H.-D.
Abstract: The characteristics of polyphosphazene based polymer electrolytes were investigated in contact to lithium metal electrodes with regard to interface stability, SEI, current-overpotential relation and kinetics of lithium deposition and dissolution. The comparative study concerned three electrolyte types: a) the pure liquid electrolyte 0.7 M LiPF6 in 1:1 (v:v) EC/DMC as reference electrolyte, b) freshly prepared dry electrolyte membranes made from poly[bis(2-(2-methoxyethoxy)ethoxy) phosphazene] (MEEP) with dissolved LiPF6 and c) a MEEP-based gel containing MEEP with 50 wt% of the above liquid electrolyte. A combination of DC current-voltage analysis, electrochemical impedance spectroscopy and optical microscopy was used to study lithium cycling, time dependent galvanostatic lithium plating/stripping and overpotential variation. A detailed model is presented which explains the observed voltage-time profile and the accompanying interface changes considering the comprehensive influences of electrolyte decomposition, changes of the interface morphology, the increase of surface roughness induced by dendrite formation (microscopically monitored) and the intermediately forming SEI (analyzed by impedance spectroscopy). Graphical abstract: Stable Li metal/Electrolyte interface The characteristics of LiPF6 in EC/DMC and dry/gel polymer based on poly[bis(2-(2-methoxyethoxy) ethoxy) phosphazene (MEEP) were investigated in contact to lithium metal electrodes with regard to interface stability, SEI, current-overpotential relation and kinetics of lithium deposition and dissolution. MEEP gel polymer develops a very favorable Li/polymer interface (less dendrites) with a more conductive and more stable SEI on the lithium metal anode as well as exhibiting a faster formation.Image 1 Highlights: Different lithium plating/stripping kinetics, morphologies and SEI properties were observed for MEEP polymer electrolytes and liquid electrolyte. MEEP electrolytes generate less dendrites compared to liquid electrolyte due to the faster SEI formation and their higher mechanical strength. MEEP gel polymer develops a favorable interface with a more conductive & stable SEI on Li metal anode compared to dry polymer/liquid electrolyte.